Cannabinoid Hyperemesis Syndrome - case report - Mazurek-Staroń, Maria; Zgardzińska-Głąb, Izabela; Michalska-Borowiec, Magdalena; Radwan-Pizoń, Aneta; Sędłak, Sylwia; Dengler-Orzechowska, Barbara; Rocka, Agata; Sudoł, Justyna (Journal of Education, Health and Sport, 2025)
In 2018, research conducted by Kantar Polska and the National Bureau for Counteracting Drug Addiction showed that marijuana was the most commonly used drug in Poland among the general population. Its usage rate was 12.1%. The age group most likely to use marijuana was 15-24 years old. Marijuana use was more common among males. Despite promising results regarding the use of medicinal marijuana for certain conditions, easier access to this drug among the young population generates the problem of addiction and the occurrence of negative effects from its use. The suspicion and diagnosis of the effects of cannabinoid intake – including cannabinoid hyperemesis syndrome – should be considered in the differential diagnosis of patients presenting to pediatric emergency departments, especially in cases with unclear etiology of symptoms, their recurrence, and the age group typical for more frequent use of this drug.